Mutational analysis of ATP7B gene and the genotype-phenotype correlation in patients with Wilson's disease in Serbia - Tomić Aleksandra; Dobričić Valerija; Novaković Ivana; Svetel Marina; Pekmezović Tatjana; Kresojević Nikola; Potrebić Aleksandra; Kostić Vladimir S. (Vojnosanitetski Pregled)
Background/Aim. Wilson’s disease (WD) is an autosomal-recessive disorder which is characterized with a marked clinical heterogeneity. The gene responsible for WD is located in 13q14.3 chromosome, contains 21 exons and codes for copper specific transporting P-type adenosinetriphosphatase (ATPase) (ATP7B). Mutations in ATP7B gene change biosynthetic and transporting role of ATPase in cell leading to damaged billiary excretion of copper and its accumulation in the liver, brain, cornea and other tissues. Until now, it has been described more than 400 mutations in ATP7B gene with characteristic geographic distribution. The aim of this study was to assess the spectrum of mutations of ATP7B gene on a large number of patients in Serbian population and to make a correlation between particular genotypes and specific phenotypes. Methods. Eighty-six consecutive patients with WD from WD Clinical Research programme were included in this study. Genetic analysis was performed by direct gene sequencing method. Results. Mutations in ATP7B gene were found in 93% analyzed patients (81.4% of all alleles analyzed). Thirteen mutations were identified, one of which (G998E) was the novel one, so far undescribed in the literature. The most frequent mutation in our population was H1069Q, which was present in 38.4% patients, and the second most frequent mutation was 2304-2305insC (11.6%). Also, a great number of gene polymorphisms of DNA sequences, which do not disturb the ATP7B gene function, was identified. Although neurological form of the disease was more frequent in the group of homozygous for H1069Q and the group of non- H1069Q carriers, there was no statistically significant difference between the groups. Conclusion. Our research showed that genetic diagnosis of WD can be done in 80% of cases by analysis of 5 most common mutations in our population, which facilitate diagnosis significantly. There was no correlation between different genotypes and specific phenotypic features of WD, the presence of psychiatric disturbances and cognitive deterioration. [Projekat Ministarstva nauke Republike Srbije, br. 175090 i br. 175091]